Toxicopathological Effects of Aluminum Chloride (AlCl3) in Reproductive System of Female Albino Mice - AL-Kaisei, Bushra I.; Humadai, Taghreed Jabbar; Al-Taee, Eman H. rY.; Alamaary, Ali N.Faraj; Salih, Anfal Mahdi M. (Journal of Kerbala for Agricultural Sciences, 2017)
The present study was designed to investigate the toxic effects of aluminum chloride AlCl3 injected intraperitonally of albino female to study the clinical signs and histopathological changes in reproductive system. (159) of Female mice in the age of puberty and weights ranged (30-35) g were used in this study which included three experiments: first experiment: - This experiment was conducted on 87 female mice, divided into 2 groups by intrapertional injection, the first group contained (15) female mice for the purpose of knowing the lowest value and the highest value in the pilot study, while (72) female mice were used for the purpose of determining the dose toxin medium lethal (LD50), and by the way probit method for the purpose of examining the symptoms of acute toxicity , severity , time of appearance and disappearance clinical sings, which estimated 1100 mg / kg of body weight, second experiment: This experiment was conducted on (36) female mice for a period of (14) days, mice were divided into two groups, as follows: 1- sub acute high toxic exposure group: -Injected with I / P high dose(221.83)mg/kg of body weight included 18 females mice 2-Control group: - Injected I / P solution Physiologic solution included (18) female mice. 3rd experiment: -This experiment was conducted on (36) female mice for a period of (60) day of the experiment, they were divided into two groups, as follows: - 1 – Sub chronic low toxic exposure group: injected I / P low dose (55.45) mg/kg of body weight included (18) females mice. 2– Control group: -injected I / P solution Physiologic and included (18) females mice. The study were conducted at days (3, 7, 14) for the sub acute toxic value exposure and at (15, 30, 60) exposure to toxic sub chronic. The study showed that the effects increased with increasing AlCL3dose and duration of exposure. Where results showed clinical signs that were depression of animal, neurological signs, diarrhea, with paralysis and suffocation and ended up comatose and death within half an hour, pathological changes characterized by degeneration and distraction of ovary with oviduct and uterus, necrosis, papillary hyperplasia of endometrial epithelial lining mostly in sub chronic toxic effects at day 60 .